The head & neck III, The larynx & carotid triangle - Brend, Hillen (Amsterdam : Elservier Science, 1995)
(Producer) Presents 9,000 images of normal anatomy and 1,200 correlative images from CT, MRI, and histology, and enables medical professionals to explore interactively the major structures of the larynx, the carotid sheath, the major part of the thyroid gland, the oro- and laryngopharynx, and the cervical spine from C2 to C7 (excluding the posterior parts of the spinous processes).
CD is available at Koleksi Media, Perpustakaan HUKM
Includes one CD-I disc and one CD-ROM
System requirements: CD-I disc: Any CD-I player upgraded with a Digital Video (DV) cartridge; television.
System requirements: CD-ROM disc: IBM-compatible PC, 386-33 CPU or better; 4 Mb internal memory, 3 Mb free disc space; Microsoft Windows 3.1; double-speed CD-ROM player; 256 col. VGA adapter; mouse.
Keywords: Neck -- anatomy & histology -- CD-ROM; Larynx -- anatomy & histology -- CD-ROM; Carotid Arteries -- anatomy & histology -- CD-ROM; Diagnostic Imaging -- CD-ROM